Heart Rate Variability During a Standard Dive: A Role for Inspired Oxygen Pressure? - Lafère, Pierre; Lambrechts, Kate; Germonpré, Peter; Balestra, Ambre; Germonpré, Faye Lisa; Marroni, Alessandro; Cialoni, Danilo; Bosco, Gerardo; Balestra, Costantino (Frontiers in Physiology, 2021)
Introduction: Heart rate variability (HRV) during underwater diving has been infrequently investigated because of environment limitations and technical challenges. This study aims to analyze HRV changes while diving at variable hyperoxia when using Open Circuit (OC) air diving apparatus or at constant hyperoxia using a Closed Circuit Rebreather (CCR). We used HRV analysis in time and frequency domain adding non-linear analysis which is more adapted to short time analysis and less dependent on respiratory rate (Sinusal respiratory arrythmia). Materials and methods: 18 males, 12 using OC (30 mfw for 20 min) and 6 using CCR (30 mfw for 40 min.). HRV was recorded using a polar recorder. Four samples of R-R intervals, representing the dive were saved for HRV analysis. Standard deviation of normal-to-normal intervals (SDNN), square root of the mean squared differences between successive RR intervals (rMSSD) and average RR intervals (RR) in Time-domain; Low frequency (LF) and high frequency (HF) in frequency domain were investigated. Non-linear analysis included Fractal Dimension (FrD). Results: SDNN and rMSSD were significantly increased during descent and at depth with OC, not with CCR. Mean RR interval was longer at depth with OC, but only during ascent and after the dive with CCR. HF power was higher than baseline during the descent both with OC and CCR, and remained elevated at depth for OC. The LF/HF ratio was significantly lower than baseline for descent and at depth with both OC and CCR. After 30 minutes of recovery, the LF/HF ratio was higher than baseline with both OC and CCR. Non-linear analysis detected differences at depth for OC and CCR. Discussion: Increased parasympathetic tone was present during diving. RR duration, SDNN; rMSSD, HF spectral power all increased during the dive above pre-dive levels. Conversely HF power decreased (and the LF/HF increased) 30 min after the dive. Using FrD, a difference was detected between OC and CCR, which may be related to differences in partial pressure of oxygen breathed during the dive.